The Angioedema Quality of Life Questionnaire (AE‐QoL) – assessment of sensitivity to change and minimal clinically important difference. Issue 8 (13th June 2016) - Weller, K.; Magerl, M.; Peveling‐Oberhag, A.; Martus, P.; Staubach, P.; Maurer, M.
Abstract: Background: The Angioedema Quality of Life Questionnaire (AE‐QoL) has recently been developed and validated as the first specific patient‐reported outcome tool to assess quality of life (QoL) impairment in recurrent angioedema patients. As of yet, its sensitivity to change and minimal clinically important difference (MCID) have not been established. Methods: Recurrent angioedema patients with chronic spontaneous urticaria or hereditary angioedema were repeatedly asked to complete the AE‐QoL along with the SF‐12 and other anchors for QoL impairment and disease activity during routine care visits. The sensitivity to change of AE‐QoL was determined by correlating changes in its scores over time with changes in the applied anchors. In addition, the MCID was determined using anchor‐based and distributional criterion‐based approaches. Results: Two hundred and seventy‐eight patients contributed data sets for analysis. Baseline AE‐QoL values were found to correlate well with SF‐12 results as well as all other applied anchors for angioedema‐related QoL impairment and disease activity. In addition, AE‐QoL score changes over time correlated significantly with changes in the above anchors, thus demonstrating its sensitivity to change. The MCID of the AE‐QoL total score was found to be six points. Conclusion: The AE‐QoL is a valuable tool to assess changes of QoL impairment in recurrent angioedema patients over time, including changes due to treatment.